Inflation Pressure in Side Branch during Modified Jailed Balloon Technique Does Not Affect Side Branch Outcomes - Tetsuya Nomura; Naotoshi Wada; Issei Ota; Satoshi Tasaka; Kenshi Ono; Yu Sakaue (Journal of Interventional Cardiology)
Objectives. This study aimed to investigate the optimal jailed balloon inflation in the side branch during the modified jailed balloon technique for bifurcated lesions. Background. The modified jailed balloon technique is one of the effective techniques to minimize the emergence of side branch (SB) compromise by preventing plaque or carina shifting during a single stent strategy in the main vessel with provisional SB treatment. However, there are no detailed studies on the method of optimal jailed balloon inflation. Methods. We analyzed 51 consecutive patients who underwent percutaneous coronary intervention (PCI) for bifurcated lesions with a modified jailed balloon technique between September 2018 and December 2020. These 51 patients were divided into two groups according to the magnitude of inflation pressure of the jailed balloon: a higher pressure (HP) group and lower pressure (LP) group. Results. No significant differences in procedural outcomes were observed between the two groups. The findings of SB compromise were relatively common with our procedure (30.0% in the HP group; 33.3% in the LP group). The patterns of SB compromise such as dissection or stenosis increase were observed at similar frequencies between them. In particular, SB dissection was noted in the SB lesion with some plaque burden, irrespective of the magnitude of the jailed balloon inflation pressure. Univariate analysis showed that calcification in the main vessel and SB lesion length was significantly associated with SB compromise. Finally, all PCI procedures were successfully completed without any provisional stent deployment in SB. Conclusions. We speculate that lesion characteristics rather than the PCI procedural factors may be critical determinants to cause SB compromise.